Crystal structure of bis(1-ethyl-6-fluoro-4-oxido-7-(piperazin-1-ium-1-yl)-1,8-naphthyridin-1-ium-3-carboxylate-κ2O,O′)copper(II) benzene-1, 4-dicarboxylate dihydrate, C38H42F2CuN8O12 - Cui Kuo; Wang Liang-Liang; Zhang Wen-Wei; Liu Fu-Xin; Zhang Wen-Jun; Fan Zhuo-Wen (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C38H42F2CuN8O12, triclinic, P1̅ (no. 2), a = 5.4709(2) Å, b = 10.4100(4) Å, c = 17.3373(6) Å, α = 95.014(2)°, β = 92.041(2)°, γ = 103.223(2)°, V = 955.96(6) Å3, Z = 1, Rgt(F) = 0.0347, wRref(F2) = 0.1125, T = 296 K.